1990
DOI: 10.1016/0014-5793(90)80622-p
|View full text |Cite
|
Sign up to set email alerts
|

Ligustrazine selectively blocks ATP‐sensitive K+ channels in mouse pancreatic β cells

Abstract: Ligustrazine potently inhibits hypoxic pulmonary vasoconstriction. This effect can be mimicked by the sulphonylurea tolbutamide, a blocker of ATP-sensitive K' channels. Here we demonstrate that ligustrazine is a specific blocker of ATP-sensitive K+ channels in mouse pancreatic fi cells.This suggests that ligustrazine may act in the pulmonary circulation by blocking ATP-sensitive K+ channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several studies have shown that ligustrazine, an alkaloid extracted from Ligusticum wallichii Franch, is a potent blocker of vasoconstriction [11]. Ligustrazine also has strong effects of scavenging cytotoxic oxygen free radicals [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that ligustrazine, an alkaloid extracted from Ligusticum wallichii Franch, is a potent blocker of vasoconstriction [11]. Ligustrazine also has strong effects of scavenging cytotoxic oxygen free radicals [12].…”
Section: Introductionmentioning
confidence: 99%